Assessment of patients radiation doses associated with computed tomography coronary angiography. (February 2023) - Salah, H.; Tamam, Nissren; Rabbaa, Mohammad; Abuljoud, Mohammad; Zailae, Ali; Alkhorayef,; Abuhadi, N.; Elshami, W.; Sulieman, A.; Bradley, D.A.
Abstract: Computed tomography coronary angiography (CTCA) has generated tremendous interest over the past 20 years by using multidetector computed tomography (MDCT) because of its high diagnostic accuracy and efficacy in assessing patients with coronary artery disease. This technique is related to high radiation doses, which has raised serious concerns in the literature. Effective dose (E, mSv) may be a single parameter meant to reflect the relative risk from radiation exposure. Therefore, it is necessary to calculate this quantity to point to relative radiation risk. The objectives of this study are to evaluate patients' exposure during diagnostic CCTA procedures and to estimate the risks. Seven hundred ninety patients were estimated during three successive years. The patient's exposure was estimated based on a CT device's delivered radiation dose (Siemens Somatom Sensation 64 (64-MDCT)). The participating physicians obtained the parameters relevant to the radiation dose from the scan protocol generated by the CT system after each CCTA study. The parameters included the volume CT dose index (CTDIvol, mGy) and dose length product (DLP, mGy × cm). The mean and range of CTDIvol (mGy) and DLP (mGy × cm) for three respective year was (2018):10.8 (1.14–77.7) and 2369.8 ± 1231.4 (290.4–6188.9), (2019): 13.82 (1.13–348.5), and 2180.5 (501.8–9534.5) and (2020) 10.9 (0.7–52.9) and 1877.3 (149.4–5011.1), respectively. Patients' effective doses were higher compared to previous studies. Therefore, the CT acquisition parameter optimization is vital to reduce the dose to its minimal value. Highlights: CCTA patients exposure and imaging protocol were assessed during three consecutive years. Patients DLP (mGy.cm) and CTDIvol (mGy) was computed for 790 CCTA procedures. CT acquisition parameter optimization is vital to reduce the dose to its minimal value. Patients' doses were slightly higher compared to previous studies.